Effectiveness of Control Time on Behavioral Changes in Complete Denture Cleaning among Elderlies - Falatehan, Niko; Denilson, Denilson (e-GiGi, 2022)
Abstract: With increasing age, a person's ability to maintain dental and oral hygiene will decrease which can result in tooth loss, therefore, a complete denture is needed to restore esthetic, masticatory, and phonetic functions. Control time can affect the success of denture usage. This study aimed to determine the effectiveness of control time on behavioral changes among elderlies by using the complete denture cleaning leaflet. This was an experimental study with a cross sectional design. Data were collected by using a questionnaire containing 15 questions. Subjects were 36 elderly living at Yayasan True Love Batam nursing home. Data collection was carried out in four meetings, namely the day before the instruction in the form of leaflet was given; control I was one day after the instruction; control II was one week after control I; and control III was two weeks after control II. The elderly behavior assessed from the questionnaire was then analyzed using the Friedman test. The results showed that the behavior of elderlies before being given instructions was in the moderate category. The highest increase of mean value of behavior was obtained after control II. The Friedman test resulted in a p value of 0.000. In conclusion, the best control time that had the most significant increase of behavior changes in complete denture cleaning was control II.Keywords: elderly; control time; leaflet; behavioral change; complete dentureÂ Â Abstrak: Dengan bertambahnya usia, kemampuan seseorang dalam menjaga kebersihan gigi dan mulut akan menurun. Keadaan ini dapat mengakibatkan kehilangan gigi sehingga diperlukan gigi tiruan lengkap (GTL) untuk mengembalikan fungsi estetik, mastikasi, dan fonetik. Waktu kontrol dapat memengaruhi keberhasilan GTL. Penelitian ini bertujuan untuk mengetahui efektivitas waktu kontrol terhadap perubahan perilaku pasien lanjut usia (lansia) dengan menggunakan leaflet pembersihan GTL. Jenis penelitian ialah eksperimental dengan desain potong lintang. Data dikumpulkan menggunakan kuesioner berisikan 15 pertanyaan. Subjek penelitian sebanyak 36 lansia di panti jompo Yayasan True Love Batam. Pengambilan data dilakukan sebanyak empat kali pertemuan yaitu pada hari sebelum diberikan instruksi berupa leaflet; kontrol I yaitu satu hari setelah instruksi; kontrol II yaitu satu minggu setelah kontrol I; dan kontrol III yaitu dua minggu setelah kontrol II. Perilaku lansia dinilai dari kuesioner kemudian dianalisis menggunakan uji Friedman. Hasil penelitian menunjukkan perilaku lansia pengguna GTL di Yayasan True Love Batam sebelum diberikan instruksi berupa leaflet termasuk dalam kategori sedang. Kenaikan nilai rerata perilaku lansia tertinggi diperoleh setelah kontrol II serta hasil uji Friedman mendapatkan nilai p=0,000. Simpulan penelitian ini ialah waktu kontrol terbaik dan yang memiliki peningkatan perubahan perilaku paling bermakna yaitu kontrol II.Kata kunci: lansia; waktu kontrol; perubahan perilaku; gigi tiruan lengkap